2022
DOI: 10.3389/fimmu.2022.856254
|View full text |Cite
|
Sign up to set email alerts
|

Annexin-A1 Tripeptide Attenuates Surgery-Induced Neuroinflammation and Memory Deficits Through Regulation the NLRP3 Inflammasome

Abstract: Neuroinflammation is a growing hallmark of perioperative neurocognitive disorders (PNDs), including delirium and longer-lasting cognitive deficits. We have developed a clinically relevant orthopedic mouse model to study the impact of a common surgical procedure on the vulnerable brain. The mechanism underlying PNDs remains unknown. Here we evaluated the impact of surgical trauma on the NLRP3 inflammasome signaling, including the expression of apoptosis-associated speck-like protein containing a CARD (ASC), cas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…MM01 inhibited inflammation by preventing ASC oligomerization and pro-caspase activation in mouse peritonitis models, but its pharmacological action and safety need further confirmation ( Soriano-Teruel et al, 2021 ). U50488H is a κ-opioid receptor agonist and annexin-A1 (ANXA1) tripeptide that effectively inhibits pyroptosis and improves PNDs by targeting the NLRP3 inflammasome via an unclear mechanism ( Song et al, 2021 ; Zhang et al, 2022 ).…”
Section: Treatmentsmentioning
confidence: 99%
“…MM01 inhibited inflammation by preventing ASC oligomerization and pro-caspase activation in mouse peritonitis models, but its pharmacological action and safety need further confirmation ( Soriano-Teruel et al, 2021 ). U50488H is a κ-opioid receptor agonist and annexin-A1 (ANXA1) tripeptide that effectively inhibits pyroptosis and improves PNDs by targeting the NLRP3 inflammasome via an unclear mechanism ( Song et al, 2021 ; Zhang et al, 2022 ).…”
Section: Treatmentsmentioning
confidence: 99%
“…ANXA1, a member of the annexin protein superfamily that mimics the effects of glucocorticoids 14 . A number of studies have highlighted a well-established role for ANXA1 in the immune system, including regulation of microglial activation, endothelial integrity and leukocyte trafficking 15 , 16 . In transient ischemic attack, nuclear accumulation of ANXA1 in microglia was associated with microglial polarization 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Toll-like receptor (TLR) plays a critical role in microglial activation. The TLR4/nuclear factor kappa B (NF-κb) signaling pathway can induce the transcription activation of various inflammatory factors, ultimately leading to apoptosis of nerve cells. ,, TAK-242 inhibits lipopolysaccharide (LPS)-mediated activation of the TLR4/NF-κb pathway, which is related to protection against transient cognitive deficits in aged animals. , Early management of neuroinflammation and oxidative stress may prevent the occurrence of some neurological disorders. With the progression of time following splenectomy, the activation of the TLR4 pathway and increases in the levels of inflammatory factors, as well as cognitive decline, are gradually reversed . However, Terrando found that the TLR4 pathway is seemingly not necessary for the occurrence of surgical trauma-induced cognitive deficits .…”
Section: Introductionmentioning
confidence: 99%